2009
DOI: 10.18553/jmcp.2009.15.6.501
|View full text |Cite
|
Sign up to set email alerts
|

Still Looking for Health Outcomes in All the Wrong Places? Misinterpreted Observational Evidence, Medication Adherence Promotion, and Value-Based Insurance Design

Abstract: Above all, the right question needs to be framed."1 To those who would argue that sophisticated statistical modeling obviates the need to consider confounding factors and alternative explanations when interpreting observational associations, Freedman's answer was simple: "The technology is relatively easy to use. … However, the appearance of methodological rigor can be deceptive."1 More contemporary guidelines for research reporting acknowledge the same understanding: when interpreting associations, multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…57 We have also noted that the "case" for the negative effect of typical copayment increases on adherence has been made primarily with research employing observational designs in which association was sometimes erroneously equated with causation; quasiexperimental (pre vs. post with comparison group) studies of typical copayment increases in commercially insured groups have generally found positive outcomes for patients and plan sponsors. 8,[58][59][60][61] Unfortunately, much of the literature on cost sharing has tended to overstate or misstate previous research findings, suggesting that cost sharing had a greater influence on medication adherence than was actually documented in the original work. For example, in discussions of cross-sectional analyses comparing higher versus lower cost sharing levels, one sometimes sees references to "price responsiveness" to " [copayment] changes" when no copayment change was measured 58 or to "adherence" outcomes from studies that included no measures of adherence; 57 and seemingly small but often substantively important discrepancies are common.…”
Section: Inaccurate Descriptions Hamper Efforts To Evaluate Vbidmentioning
confidence: 99%
See 1 more Smart Citation
“…57 We have also noted that the "case" for the negative effect of typical copayment increases on adherence has been made primarily with research employing observational designs in which association was sometimes erroneously equated with causation; quasiexperimental (pre vs. post with comparison group) studies of typical copayment increases in commercially insured groups have generally found positive outcomes for patients and plan sponsors. 8,[58][59][60][61] Unfortunately, much of the literature on cost sharing has tended to overstate or misstate previous research findings, suggesting that cost sharing had a greater influence on medication adherence than was actually documented in the original work. For example, in discussions of cross-sectional analyses comparing higher versus lower cost sharing levels, one sometimes sees references to "price responsiveness" to " [copayment] changes" when no copayment change was measured 58 or to "adherence" outcomes from studies that included no measures of adherence; 57 and seemingly small but often substantively important discrepancies are common.…”
Section: Inaccurate Descriptions Hamper Efforts To Evaluate Vbidmentioning
confidence: 99%
“…65,66 In contrast to the commentary's portrayal, RHIE authors even argued in 1987 and 1992 that their finding of "enormous potential savings" from cost sharing, with "little apparent health impact on the kind of people who typically are covered under employer health insurance," may have prompted plan sponsors to increase coinsurance and deductibles in the years immediately following the RHIE's publication, resulting in large health care cost savings nationwide. 65,67 New Observational Evidence About VBID Copayment Reduction Since publication of our earlier observations about deficiencies in research on VBID, 8,57 new copayment reduction studies using nonrandomized comparison groups have been published, 29,62,63,[68][69][70][71] and an additional study 31 measured the association between medication adherence and all-cause health What Do We Really Know About VBID? Quality of the Evidence and Ethical Considerations for Health Plan Sponsors not contain the patient subgroup counts necessary to calculate unbiased discontinuation rates for the study groups.…”
Section: What Do We Really Know About Vbid? Quality Of the Evidence Amentioning
confidence: 99%
“…39 While the recent report "Thinking Outside the Pillbox" (August 2009), also trumpeted the now-familiar song, there was recognition of the need for a systemwide approach to improving medication adherence in patients with chronic disease, citing factors such as the patient's inability to navigate the health care system, cognitive impairment, and imperfect drug regimens. 40 We may indeed be stuck with some authors using the term "therapeutic inertia," but we suggest that when this term is used that authors be specific and not attribute failure of patients to meet therapeutic goals solely to clinicians' failure to intensify treatment in a timely manner.…”
Section: Titration To Biomarker Goals-a Fool's Errand?mentioning
confidence: 99%
“…First, as noted in editorial critiques of studies that have examined the association between cost sharing and adherence, 41,42 this study is limited by its observational (nonrandomized) nature and therefore can only be interpreted as suggesting an association between cART prescription cost sharing and adherence to behavior. Eighth, race, actual income, biometric information, and mortality are unavailable within the data due to privacy protections.…”
Section: Limitationsmentioning
confidence: 99%